Glaucoma Revisited - Chaudhry, M. Lateef (Pakistan Journal of Ophthalmology, 2007)
Glaucoma being the commonest cause of irreversible blindness all over the world is rather complex disorder requiring timely detection and optimal management to preserve the remaining vision. Whatever vision has been lost is permanent and irreversible, hence the need for earliest detection and appropriate management. In our part of the world the incidence of angle closure and open angle glaucoma seems nearly equal. While the chronic simple glaucoma (POAG) is branded as slow, insidious, asymptomatic disease and angle closure glaucoma as acute symptomatic disorder, we have to bear in mind a few important facts.